2004
DOI: 10.1002/cjce.5450820424
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Resolving Reverse Emulsions in SAGD Production Systems

Abstract: The standard method for water clarification in SAGD operations involved the injection of latex polymers to break produced reverse emulsions. Operationally, this resulted in large quantities of oil in the water downstream of the first oil and water separation vessel. Problems occurred because this generated large amounts of oily solids and emulsion. This slop material represented a significant additional expenditure. Champion developed a novel approach to treat these systems and reduce slop. This program has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Arguably, o/w emulsions are favored during pre-production in the reservoir; however, in post-production they can potentially pose some operational problems requiring specific chemical treatments [70].…”
Section: Factors Affecting Sagd Performancementioning
confidence: 99%
“…Arguably, o/w emulsions are favored during pre-production in the reservoir; however, in post-production they can potentially pose some operational problems requiring specific chemical treatments [70].…”
Section: Factors Affecting Sagd Performancementioning
confidence: 99%
“…11,34−36 The addition of REBs is aimed to enhance the quality of the produced water from the SAGD emulsions through the removal of dispersed oil droplets. 12,37,38 It has been widely accepted that the extraordinary stability of the SAGD emulsions is caused by the presence of interface-active species (e.g., asphaltenes, resins, and natural surfactants). 33,39−42 These interface-active species are adsorbed at the oil/water interface and form a rigid and irreversible interfacial film.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical additives in conjunction with a high temperature separator (HTS) have been extensively applied to the demulsification process in the SAGD production. Two major types of the chemical additives, i.e., emulsion breakers (EBs) and reverse emulsion breakers (REBs), are synergistically used to achieve desirable demulsification and separation efficiency. The objective of adding EBs is to improve the dryness of produced oil by treating water-in-oil (W/O) emulsions. , A variety of EBs have been explored and commercially used in conventional demulsification technologies (e.g., surface mining process of oil sands) for decades, such as propylene oxide (PO)-polymeric ethylene oxide (EO) block copolymers, ethylcellulose, , alkylphenol resin alkoxylates, and nanoparticles. , Correspondingly, systematic studies have been conducted on the influencing factors , and demulsification mechanisms , of EBs for destabilizing the W/O emulsions, which significantly improves their development and applications in the SAGD production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field reports mostly focus on the impact of emulsion on separation and transportation of produced liquid. It has in some instances been reported that the production of oil-in-water (reverse) emulsion is common in SAGD (Bosch et al, 2004). Experimental investigations however suggest that produced liquid during SAGD is predominantly water-in-oil type emulsion (Mohammadzadeh and Chatzis, 2009;Noik et al, 2005;Sasaki et al, 2001A, 2001B;Chung and Butler, 1987).…”
Section: Introductionmentioning
confidence: 99%